Profile of mean platelet volume, neutrophil - lymphocyte ratio and platelet - lymphocyte ratio in patient with psoriasis - Khatun, Fatema; Ahmed, Zakir; Paul, Harasit K.; Amin, Zinat; Chowdhury, M. S. Z. (International Journal of Research in Dermatology, 2021)
Background: Psoriasis is a chronic, inflammatory, systemic disease. In response to therapy in psoriasis patients, the psoriasis area severity index (PASI) is used to evaluate the disease activity. However more objective laboratory tools should be developed besides PASI. In various inflammatory diseases, mean platelet volume (MPV), neutrophil-lymphocyte ratio (NLR), and platelet lymphocyte ratio (PLR) are inflammatory biomarkers that are known to be evaluated. The aim of the study was to assess the frequency of platelet activation and leukocyte infiltration by measuring MPV, NLR, and PLR. Methods: This was a case-control observational study conducted at department of dermatology and venereology at Bangabandhu Sheikh Mujib Medical University from July 2016 to December 2017. A total of 55 psoriasis cases and 55 healthy controls were included according to inclusion and exclusion criteria. Results: We have investigated a total of 55 psoriasis patients and another 55 age-sex matched control. There were 31 males (56.36%) and 24 females (43.44%) psoriasis patients in the study. The mean age of the patient was 34.27±13.44 years. Mean±standard deviation (SD) value of MPV, NLR, and PLR in our study cases were 9.92±1.21, 4.32±8.53, and 292.96±88.80 whereas in the case of control values were 9.46±0.636, 4.54±8.51, and 162.26±103.38 respectively. Conclusions: In conclusion, we suggest MPV is a strong indicator of psoriasis severity. MPV and PLR should be followed up routinely to take preventive measures against psoriasis-related micro and macro vascular thrombotic complications.